Laparoscopic salpingectomy and adhesiolysis for concomitant left-sided cornual ectopic gestation and adhesive partial intestinal obstruction: A Case Report - Usman M. Bello; Murtala Yusuf; Zainab Garba (Ntec Specialist, 2022)
Background: Cornual gestation is one of the most hazardous types of ectopic gestation. It carries a significant challenge and a greater maternal mortality risk than ampullary ectopic pregnancy. The diagnosis and treatment are challenging and frequently constitute a medical emergency. Traditionally, the treatment of cornual pregnancy has been hysterectomy or cornual resection at laparotomy. However endoscopic approach is a viable option and consists of conservative techniques such as laparoscopic cornual resection, laparoscopic cornuostomy, laparoscopic salpingectomy or hysteroscopic removal of interstitial ectopic tissue. Case presentation: We report a case of a 28-year-old multipara who had an unruptured left cornual ectopic gestation with moderate pelvic adhesions and concomitant partial intestinal obstruction. She was managed via laparoscopic adhesiolysis and left total salpingectomy. Conclusions: Cornual pregnancy occurs rarely, there is a need for early and prompt diagnosis to prevent potentially fatal complications.